Good governance in the era of global neoliberalism : conflict and depolitisation in Latin America, Eastern Europe, Asia and Africa - Demmers, Jolle, 1969-; 9; Hogenboom, Barbara (London ; New York : Routledge, 2004)
"By making use of a wide range of in-depth case studies from various developing countries and post-communist states, this book analyzes the causes and effects of neoliberal restructuring and the process of depolitization that went with it. The contributors critically examine the contradictory nature of good governance and the consequences that have been seen to go with it." "This important book provides a contribution to the literature on good governance. It will provide and interesting read for those with an interest in economics and development studies as well as being useful to policy makers and non-governmental organizations."--BOOK JACKET.
Machine derived contents note: 1 Good governance and democracy in a world of neoliberal regimes 1 -- JOLLE DEMMERS, ALEX E. FERNANDEZ JILBERTO -- AND BARBARA HOGENBOOM -- 2 The political economy of neoliberal governance -- in Latin America: The case of Chile 38 -- ALEX E. FERNANDEZ JILBERTO -- 3 'Que se vayan todos': Neoliberal collapse -- and social protest in Argentina 66 -- NORMA GIARRACCA AND MIGUEL TEUBAL -- 4 Governing Mexico's market democracy 91 -- BARBARA HOGENBOOM -- 5 Triple transition and governance in El Salvador 116 -- CHRIS VAN DER BORGH -- 6 Playing Russian roulette: Putin in search of good governance 134 -- ANDRE MOMMEN -- "7 'Good governance' can make bad government: A study of -- international anti-corruption initiatives in Bosnia-Herzegovina 161 -- DAVID CHANDLER -- 8 Clanism and predatory capitalism: The rise of -- a neoliberal nomenklatura in Ukraine 180 -- HANS VAN ZON -- 9 Between globalisation and sub-national politics: -- Russian think tanks and liberalism 203 -- ANDREY S. MAKARYCHEV -- 10 'Bad governance' under democratic rule in Taiwan 224 -- TAK-WING NGO -- 11 The political economy of recovery in Indonesia 246 -- J. THOMAS LINDBLAD -- 12 China's transition to industrial capitalism: -- Tracking institutional reform 265 -- HENK HOUWELING -- 13 From new order to new world order: Good governance -- and violence in Indonesia 287 -- JUDITH LARGE AND NICK MAWDSLEY -- 14 Good governance, privatisation and -- ethno-regional conflict in Cameroon 306 -- PIET KONINGS -- 15 Global neoliberalisation and violent conflict: -- Some concluding thoughts 331 -- JOLLE DEMMERS.
Formerly CIP.
Includes bibliographical references and index.
Altab
Keywords: Free enterprise -- Case studies; Free trade -- Case studies; Globalization -- Case studies; Structural adjustment (Economic policy) -- Case studies